Influence of negative pressure on changes in blood supply in donor zones of perforant flaps formation - Badiul , P.O.; Korpusenko , O.I.; Nor , N.M.; Korpusenko, I.V.; Rudenko, O.I. (Medicni Perspektivi, 2022)
Our study is based on the establishment of normative indicators of the effect of negative pressure on the skin of the thigh. To do this, a group of healthy volunteers was examined – 35 people: 17 women and 18 men aged 19 to 58. The study was conducted on the clinical basis of the burn centre in 2020-2021. The local vacuum was created using a negative pressure device “AGAT-Dnepr” by applying a silver-containing polyurethane sponge directly on the front surface of the thigh. The pressure (P) – 110-160 mmHg has been applied for 30 minutes. Tissue perfusion was monitored by laser Doppler flowmetry and thermal imaging research. Measurements were performed before vacuum, immediately after the end of the application of negative pressure, for three days at the same time at a constant temperature. According to the results of the cluster analysis, based on the effect of negative pressure on the thigh skin, patients with three types of reactions were identified – low, medium and high perfusion changes. The perfusion level of tissue volume per unit time increased the most rapidly: in the group of high perfusion by 45.56 (95% CI 42.09-51.96) PU; in the group of average perfusion – by 22.49 (95% CI 19.93-28.99) PU; in the low perfusion group – by 22.43 (95% CI 15.90-25.13) PU. The number of erythrocytes per unit tissue changed at a medium rate: in the high perfusion group by 57.77 (95% CI 53.05-62.48) AU; in the group of average perfusion – by 55.86 (95% CI 49.62-65.06) PU; in the low perfusion group – by 34.85 (95% CI 13.19-53.55) PU. Among those surveyed, 12 people were included in the low perfusion group (34.29%), 16 people in the medium perfusion group (45.71%) and 7 people in the high perfusion group (20.0%). Before VAC-action the ascending level of thigh skin temperature T1 ranged from 28.60 to 32.90°C and averaged 31.46 (95% CI 30.97-31.95)°C. Immediately, after the offset of the negative pressure the area of the fields of local skin temperature rise increased, the average temperature level ranged from 30.60 to 35.0°C and the average T2 was 33.59 (95% CI 33.16-34.01)°C. The temperature rise occurred on average by 2.13 (95% 1.72-2.54)°C, which corresponded to an increase of 6.77% with significant (p<0.001) statistical differences. Only 1 examined had a slight decrease in the temperature of the thigh skin from 31.9 to 31.6°C, in the rest of the examined the rise was by 6.4°С maximally, from 28.6 to 35.0°С, there was a temperature rise by 2°С or more degrees among 9 people (25.71%). After 24 hours there was a rise in local body temperature among all examined (100%), after 48 hours – among 25 (71.43%), and after 72 hours – among 21 examined (60.0%). When choosing a donor site of the perforant flaps, we recommend relying on areas which will belong to the group of indicators with high perfusion. According to the analysis, the group of high perfusion will include patients with an initial average level of perfusion in the donor areas per unit time of 15.84 (14.47-17.21) PU, the number of erythrocytes per unit tissue – 58.73 (53.44-64.02) AU and skin temperature – 29.23 (28.65-29.80)°С; to the average according to F rates – 14.36 (13.0-15.73) PU, C rates – 45.37 (39.74-51.0) AU, T rates – 28.17 (27.74-28.60)°С; to the group of low perfusion, respectively, according to F rates – 12.38 (10.74-14.0) PU, C rates – 43.89 (40.18-47.61) AU, T rates – 29.79 (29.17-30.40)°С. In general, the effect of negative pressure contributes to increased perfusion and local microcirculation in tissues, as evidenced by dynamic infrared thermography: increased “hot” skin fields, increased temperature with a temperature gradient ∆T2.1=2.13 (95% 1.72-2.54)°C and for indicators of laser Doppler flowmetry – increase in perfusion by 2.42 times (p<0.001).